MRI FINDINGS IN ACUTE WERNICKE'S ENCEPHALOPATHY, CAUSED BY HYPEREMESIS GRAVIDARUM - Anwar, Javed; Soomro, Sanaullah; Javed, Koukab; Omer, Saima (Journal of Ayub Medical College Abbottabad, 2016)
A 25-year old pregnant female with history of confusion and drowsiness for 02 days was referred by neurophysician for MRI brain. MRI demonstrated T2W/FLAIR hyper intensities in medial thalami, peri-aqueductal areas with variable diffusion restriction, apparent as hyper intense signal on DWI and no signal change on ADC mapping that was typically consistent with Wernicke's encephalopathy. A high index of suspicion is necessary, as delayed or lack of treatment can lead to high morbidity and mortality. Keywords: Wernicke's encephalopathy, MRI brain, Hyperemesis gravidarum